Chapter Michel Trivolis / Maxime Le Grec (env. 1470-1555/1556). Processus de modernisation et fin du Moyen âge en Russie - Garzaniti, Marcello (Biblioteca di Studi Slavistici, 2017)
The study aims to read the biography of Maximus the Greek in the light of the culture of humanism and the Christian renewal movements taking place between fifteenth and sixteenth century, and to highlight his role as educator in Russia. The ecclesiastic hierarchy tried to come to terms with his authoritative personality, making the most of his work to counter the influence of the Western world. At the same time, they kept him under strict control, while he intervened against anything that might undermine the authentic Christian and the monastic tradition.